Factors associated with desistance from violence in prison: an exploratory study - Olver-Ellis, Sophie (Psychology, crime & law, 2017)
Desistance from crime has been of increasing interest within criminal justice literature, but desistance from offending behaviour whilst in custodial environments has not yet been investigated. Violence within prison establishments continues to be a significant problem; therefore, this study investigated the factors that are associated with desistance from custodial violence in 63 UK Category C adult male prisoners with a record of violence in prison. Participants completed measures of eight social and subjective factors associated with desistance in community samples. Those who had desisted from prison violence for 12 months or more showed greater levels of pro-social attitudes, agency and resilience than those who persisted in violence. Agency independently predicted desistance and this was particularly the case for younger offenders. Internal shifts appeared to be supported by a positive work environment. It is concluded that in custody an internal shift in perspective is especially important for desistance, and that this can be supported by the social environment. Opportunities to intervene may be greater in younger prisoners. It is recommended that current initiatives in developing agency and positive social interaction, such as Psychologically Informed Planned Environments, are further developed.